Teacher Education Practices for Preparing Secondary-Level Preservice Teachers to Lead Whole Class Discussions - Gretchen Norland (The Advocate, 2021)
This qualitative embedded, single-case study examined the perceptions and experiences of four secondary-level preservice teachers leading whole class discussions in education classes in a private Midwestern college. Despite the research on the importance of dialogic instruction, preservice teachers are inadequately prepared to facilitate discussions. Little research exists on how to help secondary-level preservice teachers develop effective discussion skills. The significance of this study highlights an increase in secondary-level preservice teachers’ abilities to lead whole class discussion through questioning strategies correlated with Bloom’s Taxonomy (1956) and practice-based teaching methods. More research is needed on the effects of practice-based teaching methods and preparing secondary-level preservice teachers to lead discussions in real classrooms.
Keywords: Secondary-level preservice teachers; whole class discussion; Bloom& #x27; s Taxonomy; Practice-based teaching methods; lower level and higher level questions; revoicing; uptake